Significance of Streptococcus gallolyticus subsp. gallolyticus Association With Colorectal Cancer - Pasquereau-Kotula, Ewa; Martins, Mariana; Aymeric, Laetitia; Dramsi, Shaynoor (Frontiers in Microbiology, 2018)
Streptococcus gallolyticus subsp. gallolyticus Sgg (formerly known as S. bovis type I) is the main causative agent of septicemia and infective endocarditis (IE) in elderly and immunocompromised persons. It belongs to the few opportunistic bacteria, which have been strongly associated to colorectal cancer (CRC). A literature survey covering a period of 40 years (1970–2010) revealed that 65% of patients diagnosed with an invasive Sgg infection had a concomitant colorectal neoplasia. Sgg is associated mainly with early adenomas and may thus constitute an early marker for CRC screening. Sgg has been described as a normal inhabitant of the rumen of herbivores and in the digestive tract of birds. It is more rarely detected in human intestinal tract (2.5–15%). Recent molecular analyses indicate possible zoonotic transmission of Sgg. Thanks to the development of a genetic toolbox and to comparative genomics, a number of factors that are important for Sgg pathogenicity have been identified. This review will highlight the role of Sgg pili in host colonization and how their phase-variable expression contributes to mitigate the host immune responses and finally their use as serological diagnostic tool. We will then present experimental data addressing the core question whether Sgg is a cause or consequence of CRC. We will discuss a few recent studies examining the etiological versus non-etiological participation of Sgg in colorectal cancer with the underlying mechanisms.